Conservative management of paraphimosis via telecommunication: an option in the COVID-19 era? - Ahmet Alyanak; Özer Ural Çakıcı (Hygeia Press di Corridori Marinella, 2020)
Paraphimosis is a urological emergency that is best managed by a manual reduction or incision of the narrowed band when manual reduction has failed. Facilitator options for this reduction are proposed, which are mostly involved in creating a hyperosmolar environment to decrease edema in the trapped prepuce. However, all series to date and the best of the authors' knowledge have reported the reduction of the paraphimosis at hospital admission, either by manual maneuver or surgical interventions. In this report, we present two paraphimosis cases that were successfully managed by parent-education, close observation via telecommunication, and locally applied steroid and antihistaminic therapy.